Increasing Service Levels in Conference and Educational Scheduling: A Heuristic Approach - Sampson, Scott E.; Weiss, Elliott N. (Management Science, 1995)
This paper explores a technique for developing a conference (or class) schedule that maximizes the servicing of participant requests for sessions. Data regarding participant interests are collected before the time the schedule is generated. The problem contains two principal parts: (1) to feasibly assign session offerings to time periods and rooms, and (2) to assign participants to sections of multiple-offering sessions. A heuristic procedure that simultaneously solves both parts is described and tested. The procedure considers not only the participants’ requests for sessions, but also the relative importance of the various requests. Benefits of request prioritization are described. Results show that this approach can result in significantly improved participant satisfaction and equity when compared with traditional conference- and class-scheduling approaches.